(untitled) (Academicia Globe: Inderscience Research, 2022)
The article discusses issues related to the systematic organization and management of mass sports and recreational activities on an ongoing basis, aimed at creating a healthy lifestyle in society and attracting wide sections of the population, especially youth, to physical education and sports